Mitochondrial Complexes I and II Are More Susceptible to Autophagy Deficiency in Mouse β-Cells - Kim, Min Joo (Endocrinol Metab (Seoul), 2015)
BACKGROUND: Damaged mitochondria are removed by autophagy. Therefore, impairment of autophagy induces the accumulation of damaged mitochondria and mitochondrial dysfunction in most mammalian cells. Here, we investigated mitochondrial function and the expression of mitochondrial complexes in autophagy-related 7 (Atg7)-deficient β-cells. METHODS: To evaluate the effect of autophagy deficiency on mitochondrial function in pancreatic β-cells, we isolated islets from Atg7(F/F):RIP-Cre+ mice and wild-type littermates. Oxygen consumption rate and intracellular adenosine 5'-triphosphate (ATP) content were measured. The expression of mitochondrial complex genes in Atg7-deficient islets and in β-TC6 cells transfected with siAtg7 was measured by quantitative real-time polymerase chain reaction. RESULTS: Baseline oxygen consumption rate of Atg7-deficient islets was significantly lower than that of control islets (P<0.05). Intracellular ATP content of Atg7-deficient islets during glucose stimulation was also significantly lower than that of control islets (P<0.05). By Oxygraph-2k analysis, mitochondrial respiration in Atg7-deficient islets was significantly decreased overall, although state 3 respiration and responses to antimycin A were unaffected. The mRNA levels of mitochondrial complexes I, II, III, and V in Atg7-deficient islets were significantly lower than in control islets (P<0.05). Down-regulation of Atg7 in β-TC6 cells also reduced the expression of complexes I and II, with marginal significance (P<0.1). CONCLUSION: Impairment of autophagy in pancreatic β-cells suppressed the expression of some mitochondrial respiratory complexes, and may contribute to mitochondrial dysfunction. Among the complexes, I and II seem to be most vulnerable to autophagy deficiency.